Investigación Acción En Un Entorno Educativo: Programa Para Promover Creencias Positivas Hacia Una Cultura De Paz Y De Prevención A La Violencia - Trejos, Analinnette Lebrija (European Scientific Journal, ESJ, 2016)
The objective of the research is validating a program to promote positive beliefs towards a culture of peace and prevention of school violence from a psychological perspective and health promotion. Beliefs are understandings and assumptions about the world that are perceived as truths and that underlie the attitudes and decision making of individuals. We carried out a total of 6 workshops, of two hours each given weekly, and two evaluation sessions, to 43 students divided into a study group and a control group, with a simple random sample type. During the week, we used process-measuring instruments. The workshops were based on competence of life and education for peace. The study was conducted in a school located in Panama City. The subjects were teenagers from eighth grade (mid-school), aged 13 to 15 years. The study is a pretest – posttest study with control group, action research that allowed reflection and participation of students on the issue of violence. Quantitative and qualitative results indicate that the program managed to positive change the beliefs of students towards violence; the results and the theoretical background support that a change of attitudes in the long-term requires that these types of Programs are embedded in the academic process as a constant and systematic element.